Gastric cancer in pregnancy – diagnostic and therapeutic dilemma: Case Report: Rak želodca v nosečnosti – diagnostična in terapevtska dilema: prikaz primera - Kuder, Lucija; Dovnik, Andraž; Horvat, Matjaž; Takač, Iztok (Acta Medico-Biotechnica, 2021)
Background: Gastric cancer during pregnancy is a rare disease that is difficult to diagnose due to the overlapping symptoms of cancer and normal pregnancy.Methods: We present the case of a 31-year-old patient who was admitted in the 36th week of pregnancy with complaints of digestive disturbance, nausea and vomiting. Severe sideropenic anemia and the presence of blood in stools prompted us to perform gastroscopy, which showed an exulcerated lesion of the lesser curvature of the stomach. Histology revealed poorly differentiated adenocarcinoma with mixed tubular and signet ring cells.Results: Cesarean section followed by total gastrectomy with dissection of the regional lymph nodes and omentec tomy was performed on the 10th day after admission. The patient refused postoperative radiotherapy and chemotherapy and died 11 months and 2 weeks after gastric resection.Conclusion: There are no approved guidelines for the management of gastric cancer during pregnancy. Treatment is determined according to the gestational age of the fetus and the extent of gastric cancer at the time of diagnosis. The patient’s wishes must also be taken into consideration. Non-invasive methods should be used during pregnancy and invasive methods should be avoided whenever possible.
Keywords: Gastric cancer; Pregnancy; cesarean section; gastrectomy; lymphadenectomy